Beyond donor eligibility: nutritional and lifestyle heterogeneity and implications for long-term donor health preservation - Elisa Mazza; Samantha Maurotti; Yvelise Ferro; Francesca Rita Noto; Carmelo Pujia; Nancy Paone; Alessia Sestito; Marta Moraca; Ilda Fatima Martino; Arturo Pujia; Tiziana Montalcini (Frontiers in Nutrition, 2026)
Background Blood donor eligibility is essential for donation safety, but it may not fully capture nutritional, metabolic, and lifestyle-related vulnerabilities that can affect donor health over time. As transfusion systems increasingly rely on regular donors, identifying modifiable factors that may support long-term donor health and retention is becoming increasingly relevant. This study aimed to characterize nutritional and lifestyle heterogeneity, peri-donation dietary behaviors, and donation-related outcomes in adult blood donors. Methods This cross-sectional survey used a structured online questionnaire assessing anthropometric characteristics, lifestyle factors, habitual dietary intake, nutrition-related awareness, peri-donation dietary behaviors, self-reported history of iron deficiency, and post-donation symptoms. Dietary profiles were identified using principal component analysis followed by k-means clustering. Multivariable logistic regression models were used to explore factors associated with iron deficiency history and post-donation symptoms. Results The study included 698 adult blood donors. Overweight and obesity affected nearly half of the cohort and were more frequent among men and older donors, whereas women more frequently reported iron deficiency history and post-donation symptoms. Three dietary profiles were identified: Western/ultra-processed, Mediterranean-like, and mixed beverage-oriented. Younger donors were more frequently represented in less favorable dietary and lifestyle profiles, whereas older donors showed more favorable dietary habits despite a higher prevalence of overweight/obesity. In multivariable analyses, female sex was independently associated with iron deficiency history (OR 4.62, 95% CI 3.20–6.68; p < 0.001) and post-donation symptoms (OR 3.07, 95% CI 2.09–4.52; p < 0.001), while increasing age was inversely associated with post-donation symptoms (OR 0.73 per 10-year increase, 95% CI 0.64–0.84; p < 0.001). Dietary pattern membership was not independently associated with either outcome. Peri-donation dietary changes were reported more frequently before donation than after donation. Discussion These findings suggest that adult blood donors represent a nutritionally and metabolically heterogeneous population despite donation eligibility. These findings support the potential relevance of structured nutritional counseling, lifestyle-oriented prevention, and recovery-focused recommendations within donor care pathways, although their impact on long-term donor health, continued eligibility, and donor retention should be evaluated in future prospective and interventional studies.